2002
DOI: 10.1046/j.1365-2621.2002.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wild and cultured gilthead sea bream (Sparus aurata); composition, appearance and seasonal variations

Abstract: Major quality parameters, such as muscle composition, fat deposition, muscle fatty acid composition and external appearance were studied in wild and cultured gilthead sea bream. Muscle fat content and total depot fat (peritoneal and perivisceral fat) indicated a seasonal variation with minimum values observed in late spring and maximum in late summer. Gonadosomatic indices of cultured fish were lower than those found in wild specimens. Lipid content of cultured sea bream was much higher than that of wild fish.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
177
13
40

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(282 citation statements)
references
References 32 publications
52
177
13
40
Order By: Relevance
“…Unlike wild 374 populations, farmed fish live inside the cages with a 375 periodic feeding rate and easily available food, 376 suggesting that foraging is different from wild fish 377 (Arabaci et al, 2010). Therefore, the morphological 378 differences found in this study between wild and 379 farmed seabream agree with those differences found 380 by Grigorakis et al (2002) where wild seabream 381 presented lower body height, sharper snout and more 382 spindle-shaped body than cultured seabream. More-383 over, such differences could be partly explained by 384 dietary shifts, which induce changes on the body 385 shape (Keast, 1978), influencing prey selection 386 and catch efficiency (Mérigoux & Ponton, 1998).…”
Section: U N C O R R E C T E D P R O O F U N C O R R E C T E D P R O O Fsupporting
confidence: 79%
“…Unlike wild 374 populations, farmed fish live inside the cages with a 375 periodic feeding rate and easily available food, 376 suggesting that foraging is different from wild fish 377 (Arabaci et al, 2010). Therefore, the morphological 378 differences found in this study between wild and 379 farmed seabream agree with those differences found 380 by Grigorakis et al (2002) where wild seabream 381 presented lower body height, sharper snout and more 382 spindle-shaped body than cultured seabream. More-383 over, such differences could be partly explained by 384 dietary shifts, which induce changes on the body 385 shape (Keast, 1978), influencing prey selection 386 and catch efficiency (Mérigoux & Ponton, 1998).…”
Section: U N C O R R E C T E D P R O O F U N C O R R E C T E D P R O O Fsupporting
confidence: 79%
“…This finding indicates that the cultured fishes were influenced by their feed, because both the juvenile and young S. schlegeli were fed by artificial feeds dry pellets , which included high levels of plant oils, such as soybean oil rich in 18:2n-6, while cultured adult fishes were fed by natural raw fish such as sardine Sardinops melanostictus and Japanese anchovy Engraulis japonicus . The same high levels of 18:2n-6 were also observed in other cultured fishes for freshwater fish 28,29 ; for marine fish 4,5,7,10 .…”
Section: Fatty Acid Composition In Tag Depot Lipids Of Juvenile and Ysupporting
confidence: 76%
“…Wild sea bream also showed higher muscle protein levels, which was probably due to their significantly lower fat content (Grigorakis et al 2002). Periago et al (2005) reported similar protein contents of wild and farmed sea bass.…”
Section: Discussionmentioning
confidence: 96%
“…Periago et al (2005) observed similar muscle fat contents in the farmed and wild sea bass. On the contrary, some studies on other fish species showed a higher muscle fat content in the farmed than in the wild counterparts (Alasalvar et al 2002;Grigorakis et al 2002;Cejas et al 2003;Olsson et al 2003;Rodríguez et al 2004;Periago et al 2005;Mnari et al 2007).…”
Section: Discussionmentioning
confidence: 96%